Does Extracellular DNA Production Vary in Staphylococcal Biofilms Isolated From Infected Implants versus Controls?. Issue 8 (August 2017) - Zatorska, Beata; Groger, Marion; Moser, Doris; Diab‐Elschahawi, Magda; Lusignani, Luigi Segagni; Presterl, Elisabeth
Abstract: Background: Prosthetic implant infections caused by Staphylococcus aureus and epidermidis are major challenges for early diagnosis and treatment owing to biofilm formation on the implant surface. Extracellular DNA (eDNA) is actively excreted from bacterial cells in biofilms, contributing to biofilm stability, and may offer promise in the detection or treatment of such infections. Questions/purposes: (1) Does DNA structure change during biofilm formation? (2) Are there time‐dependent differences in eDNA production during biofilm formation? (3) Is there differential eDNA production between clinical and control Staphylococcal isolates? (4) Is eDNA production correlated to biofilm thickness? Methods: We investigated eDNA presence during biofilm formation in 60 clinical and 30 control isolates of S aureus and S epidermidis. The clinical isolates were isolated from patients with infections of orthopaedic prostheses and implants: 30 from infected hip prostheses and 30 from infected knee prostheses. The control isolates were taken from healthy volunteers who had not been exposed to antibiotics and a hospital environment during the previous 3 and 12 months, respectively. Control S epidermidis was isolated from the skin of the antecubital fossa, and control S aureus was isolated from the nares. For the biofilm experiments the following methods were used to detect eDNA: (1) fluorescent staining with 4′, 6‐diamidino‐2‐phenylindole (DAPI), (2) eDNA extraction using a commercial kit, and (3) confocal laser scanning microscopy for 24‐hour biofilm observation using propidium iodide and concanavalin‐A staining; TOTO ® ‐1 and SYTO ® 60 staining were used for observation and quantification of eDNA after 6 and 24 hours of biofilm formation. Additionally antibiotic resistance was described. Results: eDNA production as observed by confocal laser scanning microscopy was greater in clinical isolates than controls (clinical isolates mean ± SD: 1.84% ± 1.31%; control mean ± SD: 1.17% ± 1.37%; p < 0.005) after 6 hours of biofilm formation. After 24 hours, the amount of eDNA was greater in biofilms of S epidermidis than in biofilms of S aureus ( S aureus mean ± SD: 1.35% ± 2.0%; S epidermidis mean ± SD: 6.42% ± 10.6%; p < 0.05). Clinical isolates of S aureus and S epidermidis produced more eDNA than control isolates at 6 hours of biofilm formation. The extraction method also showed that clinical isolates produced substantially greater amounts of eDNA than controls. Conclusions: S aureus and S epidermidis exhibit a differential production of DNA with time. Clinical isolates associated with implant infections produce greater amounts of eDNA than controls. Future research might focus on the diagnostic value of eDNA as a surrogate laboratory marker for biofilm formation in implant infections. Clinical relevance: eDNA should be considered as a potential future diagnostic tool or even a possible target to modify biofilms for successful treatment of biofilm‐associated infections.